Association between depression or anxiety symptoms and immune-inflammatory characteristics in in-patients with tuberculosis: A cross-sectional study - Liu, Xiangmin; Bai, Xinyu; Ren, Rong; Tan, Lu; Zhang, Ye; Lan, Huizhen; Yang, Qianlan; He, Jianqing; Tang, Xiangdong (Frontiers in Psychiatry, 2022)
Background: Depression and anxiety are major psychological issues among patients with tuberculosis (TB) owing to chronic and complex treatments, have been reported to be closely correlated with immune and inflammation. However, the association of peripheral immune-inflammatory characteristics with depression-anxiety symptoms in in-patients with TB has rarely been reported. Methods: A cross-sectional study of 338 in-patients with TB from 3 hospitals in China were enrolled to investigate their depression and anxiety status by using the nine-item Patient Health Questionnaire (PHQ-9) and seven-item Generalized Anxiety Disorder Scale (GAD-7). Participants were divided into four groups according to the score of scales, and subgroup comparisons were made to study the differences in demography and immune-inflammatory characteristics. Logistic analysis was performed to explore factors related to depression and anxiety symptoms. Results: Depression and anxiety prevalence among patients with TB was 47.9% and 42.6%, respectively. Furthermore, 38.5% of patients reported a comorbidity of depression and anxiety symptoms. The counts of CD3, CD4, CD8, and lymphocytes decreased, whereas those of neutrophils, platelets, and peripheral blood cells and their derived indices increased among TB patients with depression-anxiety in comparison with those without symptoms (p < 0.05). Increasing age, lower income ( monthly income ≤3000 yuan ), divorced or widowed, drug resistance, and higher systemic immune inflammation index (SII) were significantly associated with depression-anxiety symptoms (p < 0.05). Conclusion: Approximately half of the patients with TB suffered from depression or/and anxiety symptoms. Patients with depression-anxiety present worse immune-inflammatory indicators compared to those without symptoms. We emphasized the importance of paying attention to the dysfunction of immune-inflammation process of TB patients with depression-anxiety symptoms. Especially, SII has a potential application value in guiding the evaluation of TB-related depression-anxiety owing to its convenience, being economical and easily accessibility.